Prevalence of Depression Among Adolescents in the U.S. From 2009 to 2019: Analysis of Trends by Sex, Race/Ethnicity, and Income - Daly, Michael (Journal of adolescent health, 2022)
Major depression is a leading cause of disability and represents a significant health concern for adolescents. Evidence of temporal trends in adolescent depression stratified by sociodemographic characteristics is needed. This study drew on 11 years of the National Survey on Drug Use and Health (N = 167,783), a nationally representative survey of adolescents aged 12–17 years conducted between 2009 and 2019. The prevalence of past-year major depressive episode (MDE) increased by 7.7 percentage points from 8.1% to 15.8% between 2009 and 2019. MDE increased by 12 percentage points from 11.4% to 23.4% among girls. The gender difference in the prevalence of MDE increased from 6.4% to 14.8% between 2009 and 2019. Black participants experienced a comparatively small increase in depression (4.1%). Since 2009 there has been a sharp and sustained increase in depression among adolescent girls in the U.S. This concerning trend highlights the critical importance of directing prevention and intervention efforts toward this group.